用于糖衣机的非正交锥齿轮设计 - 黄大宇; 付晓莉 (Jixie chuandong)
Through adding a orthogonal bevel gearpair,traditional type of coating machine is advanced.The design work of non-orthogonal bevel gears of coating machine includes calculation of the geometric parameters,Calculation of bending fatigue strength and contact fatigue strength.That design overcomes shortcomings of structure bulkiness,installation inconvenience and working unsteadiness from the leaning setting of traditional speed reducer.